Ekstrak Daun Pandan Sebagai Inhibitor Korosi Baja St37 Dalam Larutan NaCl 3% dengan Suhu Perendaman 27°C dan 40°C - Siti Fatkhul Ulum; Ediman Ginting; Simon Sembiring (Journal of Energy, Material, and Instrumentation Technology, 2021)
The extract of pandan leaf used as corrosion inhibitor of St37 steel in NaCl 3% solution. To determine the effect of inhibitor concentration and immersion temperature on steel corrosion is done with variation of inhibitor concentration there were 0, 1,8, 1,2, and 1,4% and temperature variation is 27°C and 40°C. Corrosion rate testing is done by weight loss method. Increased corrosion rate along with increasing sample weight loss. Inhbitor pandan leaf extract were the most efficient at concentration of 1.2% with soaking temperature at 27°C and 40°C. Samples were also in the characterization of XRD and SEM-EDS. The XRD results showed that the highest Fe peak was formed in a sample using a 1.2% inhibitor concentration and the lowest Fe peak in the sample without inhibitor. The SEM characterization results also showed that in samples without inhibitors look more corroded, and in samples using 1.2% inhibitor concentrations look slightly corroded. These results were reinforced by the percentage of corrosion products shown in EDS results.